2015
DOI: 10.1111/1744-9987.12276
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Epicardial Adipose Tissue, Inflammation and Volume Markers in Hemodialysis and Transplant Patients

Abstract: Cardiovascular (CV) diseases are still the most important cause of morbidity and mortality in both patients receiving hemodialysis (HD) treatment and individuals with renal transplantation (Rtx). Measurement of epicardial adipose tissue (EAT) thickness is an easily applied, cheap, and useful recent method predicting increased CV risk. We aimed to compare EAT changes in HD and Rtx patients and the association between EAT and inflammatory and CV volume markers in both groups. A total of 124 patients: 45 Rtx, 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In line with our finding, Kimak et al 59 found increased TG levels in KT patients than those of the controls. However, Tsai et al 47 reported increased TC levels and C¸olak et al 60 did not find any significant differences between the KTR, HD, and the control groups.…”
Section: Discussionmentioning
confidence: 91%
“…In line with our finding, Kimak et al 59 found increased TG levels in KT patients than those of the controls. However, Tsai et al 47 reported increased TC levels and C¸olak et al 60 did not find any significant differences between the KTR, HD, and the control groups.…”
Section: Discussionmentioning
confidence: 91%
“…After the suggestion of EFT use in the prediction of CVD risk assessment, Karohl et al [39] reported that EFT may be useful and correlated with myocardial perfusion for screening CKD patients prior to renal transplantation in order to predict future cardiovascular risk. Only one report by Colak et al [17] assessed the role of EFT in renal transplant patients and they concluded that EFT is correlated with left ventricle mass index.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that EFT is a predictor of CVD in both non uremic and uremic populations, such as in peritoneal dialysis (PD) and hemodialysis (HD) patients [14][15][16]. However, only one study mentioned that EFT is lower in RT recipients compared to HD patients [17]. At present there are not enough data about EFT and cardiovascular disease in RT recipients.…”
mentioning
confidence: 99%
“…41,42 Recent studies have shown that EAT is potentially modifiable in hemodialysis (HD) patients. Wilund et al 43 showed EAT thickness could be reduced with exercise and Colak et al 44 showed EAT thickness was significantly reduced in renal transplant patients. Experimental treat-…”
Section: Patient Characteristicsmentioning
confidence: 99%